The Role of Government in Reducing Stunting in Indonesia, Case Study: Optimization of BKKBN in Sukoharjo District - Suhita, Damayanti; Winduro, Wirid; Raharjo, Farco (International Journal of Sustainable Applied Sciences, 2023)
Indonesia is included in the list of countries with poor nutritional status, according to the World Health Organization (WHO). In 2019, the stunting rate in Indonesia was 27.6%. As a multidimensional problem, stunting requires cross-sectoral solutions. At the regional level, Indonesia has a Population and Family Planning Agency (BKKBN), which is specifically tasked with solving this problem. One area with a history of success in overcoming stunting in Indonesia is Sukoharjo Regency. This research examines the role of the government in Sukoharjo Regency, through the BKKBN, in making various efforts to reduce stunting rates. The research method is qualitative research with an empirical approach. Research data was collected through in-depth interviews, observation, and documentation, then analyzed using interactive analysis techniques. The research results found that the main steps taken were: deploying family cadres to socialize about gynecological health with prospective brides and grooms. The government utilizes technical and strategic regulations and carries out budgetary interventions to maximize the reduction in stunting rates.